UPAYA GURU DALAM MENANAMKAN NILAI-NILAI MODERASI BERAGAMA DI TPQ NGERANG TAMBAKROMO-PATI - Abdul Qowim; Yuni Suprapto; Dany Miftah M. Nur (Tunas Nusantara, 2020)
Qur’an Learning Institution (TPQ) is an informal institution under of the ministry of religion, such as Ngerang’s TPQ. Ngerang’s TPQ have three educational staff whit 62 students, as for the Ngerang’s TPQ activities direct teaching and learning to various moderation values, namely the implementation of study hour, learning quashes, manners with teachers and study partners. The three activities reflect the moderating values of tolerance, fairness and balance. While the method used in this reaches is qualitative whit the intention of understanding what phenomena the subject is experiencing. So that researchers are able to see the object’s effort in engaging in it.